Estimating the Reduction in Future Fleet-Level CO2 Emissions From Sustainable Aviation Fuel - Jain, Samarth; Chao, Hsun; Mane, Muharrem; Crossley, William A.; DeLaurentis, Daniel A. (Frontiers in Energy Research, 2021)
With rising concerns over commercial aviation's contribution to global carbon emissions, the aviation industry faces tremendous pressure to adopt advanced solutions for reducing its share of CO2 emissions. One near-term potential solution to mitigate this global emissions situation is to operate existing aircraft with sustainable aviation fuel (SAF); this solution requires almost no modification to current aircraft, making it the "quickest'' approach to reduce aviation carbon emissions, albeit the actual impact will be determined by the degree to which airlines adopt and use SAF, the ticket price impact of SAF, and the future growth of travel demand. This article presents research results that estimate the expected fleet-wide emissions of future airline operations using SAF considering various projected traveler demand and biofuel penetration/utilization levels. The work demonstrates an approach to make these predictions by modeling the behavior of a profit-seeking airline using the Fleet-Level Environmental Evaluation Tool (FLEET). FLEET's model-based predictions rely upon historically-based information about US-touching airline routes and passenger demand served by US flag-carrier airlines available from the Bureau of Transportation Statistics to provide the basis for predictions of future travel demand, aircraft fleet mix, and aircraft operations. Considering five future SAF scenarios and two future passenger demand projection scenarios, this work estimates the future fleet-level CO2 emissions, along with predicting the demand served and trips flown. Results show that the future fleet-level CO2 emissions for all scenarios with SAF are lower than the baseline scenario with no SAF, for all demand projection scenarios. The passenger demand served and the trips flown for a given SAF scenario depends on the SAF price and the biofuel penetration levels. This shows that even if airlines serve a higher passenger demand for some future scenarios, the carbon emissions could still be lower than the current baseline scenario where airlines only use conventional jet fuel.